2017
DOI: 10.1186/s13018-017-0590-3
|View full text |Cite
|
Sign up to set email alerts
|

Modified pedicle screw–rod fixation as a minimally invasive treatment for anterior pelvic ring injuries: an initial case series

Abstract: BackgroundUnstable pelvic ring injuries often involve high mortality and morbidity. This study was aimed to evaluate the modified minimally invasive pedicle screw–rod fixation for anterior pelvic ring injuries, in the respects of its feasibility, merits, and limitations.MethodsTwenty-three patients with unstable pelvic ring injuries underwent the modified anterior pedicle screw–rod fixation, with or without posterior fixation. The clinical outcomes were assessed using Majeed scores, and the quality of reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…No surgical site infection, loss of fixation, and loosening of implants were found in modified PSRF group compared with those in APEF group. LFCN is an easily injured tissue during the tissue dissection, placement of the rod, and the fixation removal [ 2 ]. In the current study, its irritation was observed in three patients (3/21, 14.3%) in modified PSRF group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No surgical site infection, loss of fixation, and loosening of implants were found in modified PSRF group compared with those in APEF group. LFCN is an easily injured tissue during the tissue dissection, placement of the rod, and the fixation removal [ 2 ]. In the current study, its irritation was observed in three patients (3/21, 14.3%) in modified PSRF group.…”
Section: Discussionmentioning
confidence: 99%
“…Accounting for only 6% of all fractures, the high-energy pelvic ring fractures often lead to serious consequences with high mortality and morbidity [ 1 ]. While a variety of treating methods have been employed, successful management of unstable pelvic fractures remains a challenge to orthopedic surgeons [ 2 ]. As a quick and easy fixation method, anterior pelvic external fixation (APEF) can stabilize the disrupted pelvic ring rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Although various approaches have been investigated to acquire bone marrow [ 1 , 19 , 20 ], limited evidence exists on the safety and quality of these techniques. Utilizing fluoroscopic guidance, a newly described approach to BMA was described as a “teardrop merging” view that allows for easy and safe passage of a needle trajectory from the PSIS to AIIS [ 21 - 23 ]. Our study utilized 3D reconstructed CT images of the pelvis and sacrum to characterize and validate the safety and area of bone encountered during BMA from this new technique.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior pelvic ring stabilization can be achieved by external fixation or internal fixation. The internal fixation methods include a plate [3], an antegrade or retrograde screw [4], a subcutaneous pelvic bridge by the occipitocervical spinal implant [5], an anterior pelvic internal fixator with supra-acetabular spinal pedicle screws and a subcutaneous connecting rod (INFIX), or modifications of the INFIX [68].…”
Section: Introductionmentioning
confidence: 99%